2013
DOI: 10.1523/jneurosci.5521-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of the Cerebellum in Gamma-Band Synchronization of the Sensory and Motor Cortices

Abstract: The cerebellum is an essential structure for the control of movement. It sends abundant ascending projections to the cerebral cortex via the thalamus, but its contribution to cortical activity remains largely unknown. Here we studied its influence on cortical neuronal activity in freely moving rats. We demonstrate an excitatory action of the cerebellum on the motor thalamus and the motor cortex. We also show that cerebellar inactivation disrupts the gamma-band coherence of local field potential between the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 45 publications
7
91
0
3
Order By: Relevance
“…In rats, under physiological conditions, the cerebellum modulates cortico-striatal plasticity through these connections [52], and the same pathway can also transmit aberrant cerebellar activity to basal ganglia, generating dystonia and dyskinesias in animals. Cerebellum also modulates cortical sensorimotor integration [167, 168] and is important for acquiring and maintaining [169] new cortico-spinal integrations. In young healthy humans, non-invasive stimulation studies demonstrated that cerebellum exerts a bidirectional modulation only on heterosynaptic motor cortex (M1) plasticity [170], which is dependent on peripheral sensory information reaching the M1 through complex polysynaptic pathways [171].…”
Section: Cerebellar Modulation Of Cortical Plasticity In Basal Ganglimentioning
confidence: 99%
“…In rats, under physiological conditions, the cerebellum modulates cortico-striatal plasticity through these connections [52], and the same pathway can also transmit aberrant cerebellar activity to basal ganglia, generating dystonia and dyskinesias in animals. Cerebellum also modulates cortical sensorimotor integration [167, 168] and is important for acquiring and maintaining [169] new cortico-spinal integrations. In young healthy humans, non-invasive stimulation studies demonstrated that cerebellum exerts a bidirectional modulation only on heterosynaptic motor cortex (M1) plasticity [170], which is dependent on peripheral sensory information reaching the M1 through complex polysynaptic pathways [171].…”
Section: Cerebellar Modulation Of Cortical Plasticity In Basal Ganglimentioning
confidence: 99%
“…The cerebellum is strongly and reciprocally connected with the cerebral cortex via the thalamus, pons, mesodiencephalic junction, and inferior olive, and the reverberating activity in this loop is heavily subject to the sleep-wake state [53][54][55]. At the onset of natural sleep, cerebellar nuclei neurons in cats show irregular, long bursts of spikes that are coherent with slow waves in the ventral lateral nuclei of the thalamus [56,57].…”
Section: Sleep-stage-dependent Cortico-cerebellar Connectivitymentioning
confidence: 99%
“…Coherence between oscillations and interactions between cerebellum and cerebrum also exist during natural spontaneous behavior and/or sensorimotor tasks in awake mice, rats, monkeys, and humans [44,55,61,62]. Still, it remains to be elucidated which parts of the cortico-cerebellar loop provide the most dominant impact on reverberating activity in the awake state as well as during various sleeping stages.…”
Section: Sleep-stage-dependent Cortico-cerebellar Connectivitymentioning
confidence: 99%
“…16,19,23,24 Functionally, gamma oscillations in neuronal networks bind neurons into a common temporal regime during higher brain functions like motor behavior, sensory perception, or memory formation. 7,[25][26][27][28] The synchronizing effect of gamma oscillations permits the coordinated activation of defined sets of neurons, which constitute functional ensemblesthe putative information-carrying multicellular subsets of neuronal networks. 9,11,29 Moreover, the precise timing of action potentials is central for use-dependent synaptic plasticity and, thus, supports learning and memory formation.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%